Multiband planar printed monopole antenna with defected reflector for wireless communication system - Ramli, Mohamad Hafize; Abd. Aziz, Mohamad Zoinol Abidin; Dahalan, Abdul Halim; Othman, Mohd Azlishah; Sulaiman, Hamzah Asyrani (Asian Research Publishing Network (ARPN), 2015)
In this paper, a multi-band planar printed monopole antenna with defected reflector for wireless communication system is presented. The antenna has been designed based on meander lines monopole printed elements and the rectangular ground structure with defected reflector above the proposed antenna. The each element of meander lines is designed with a half wavelength to radiate at a frequency of 3.6 and 5.8 GHz for Wireless Local Area Network (WLAN) application. The 50 ohm probe feed SMA type is used to feed the signal into the antenna structure. The proposed antenna is designed and simulated by using Computer Simulation Technology (CST) software. The antenna performance is analyzed in term of the return loss, bandwidth, gain, directivity, and radiation pattern at the design frequency. The bandwidth of reflection coefficient which are less than - 10 dB can be seen at (305 and 125) MHz, (248 and 359) MHz and (267 and 197) MHz for 2.4, 3.6 and 5.8 GHz for with/out defected reflector. The additional defected reflector helps to improve the return loss ,bandwidth, gain and directivity.